Interfirm Relationships and Business Performance* - Cai, Jing; Szeidl, Adam (Quarterly Journal of Economics, 2018)
We organized business associations for the owner-managers of young Chinese firms to study the effect of business networks on firm performance. We randomized 2,820 firms into small groups whose managers held monthly meetings for one year, and into a "no-meetings" control group. We find the following. (i) The meetings increased firm revenue by 8.1%, and also significantly increased profit, factors, inputs, the number of partners, borrowing, and a management score. (ii) These effects persisted one year after the conclusion of the meetings. (iii) Firms randomized to have better peers exhibited higher growth. We exploit additional interventions to document concrete channels. (iv) Managers shared exogenous business-relevant information, particularly when they were not competitors, showing that the meetings facilitated learning from peers. (v) Managers created more business partnerships in the regular than in other one-time meetings, showing that the meetings improved supplier-client matching.